130 CHARACTERISTICS AND OUTCOMES OF OLDER NURSING HOME RESIDENTS ATTENDING AN EMERGENCY DEPARTMENT. (25th October 2022) - Fallon, A; Noonan, C; Kennelly, S
Abstract: Background: Older nursing home (NH) residents are among the most vulnerable members of society, often with multiple comorbidities and complex care needs. The Emergency Department (ED) is a common point of access to the acute hospital for NH residents. This study aims to review characteristics and outcomes of older NH residents presenting to ED over one year. Methods: A prospective cohort study was carried out. NH residents aged 50 years and older attending ED of a university teaching hospital over one year (01/10/2019-30/09/2020) were included. Data on demographics, comorbidities, functional status, frailty and details of ED attendance were collected. Results: There were a total of 515 ED attendances by 341 NH residents over one year. Mean age was 76.3 years (50-103 years; SD ± 10.9). 50.9% (n=262) were female. Mean Charlson Comorbidity Index (CCI) was 5 (0-12; SD ± 2.1). 46.6% (n=240) had a dementia diagnosis. A mean of 12.6 medications (0-31; SD ± 5.3) were prescribed in the NH. Mean Clinical Frailty Score (CFS) was 6.5 (3-9; SD ± 0.9). Mean Barthel Index (BI) was 8.9 (0-20; SD ± 6.0). 38.3% (n=197) of presentations occurred "in-hours". Mean Manchester Triage Score (MTS) was 2.54 (1-5; SD ± 0.7) with 92.0% (n=474) scoring 1-3. Delirium was documented in 31.8% (n=164). Mean ED Length of Stay (LOS) was 13.7hours (0-80hours; SD ± 11.0). 14.6% (n=75) were discharged without follow-up. 61.2% (n=315) were admitted to hospital. Mean hospital (LOS) was 9.7days (0-191 days) and 8.7% (n=47) of those admitted died in hospital. 12 months after ED presentation, 40.4% (n=138) of the cohort had died. Conclusion: NH residents are a frail group, with high levels of multimorbidity, polypharmacy and significant care needs. This complexity is reflected in the numbers requiring urgent review on attendance, rates of delirium, ED LOS and hospital admission rates. Dedicated NH liaison teams may enhance care and improve outcomes for this cohort.